Complete mitogenome characteristics and phylogenetic analysis of traditional Chinese medicinal plant Tinospora sagittata (Oliv.) Gagnep. from the Menispermaceae family - Jing Zhao; Zi-Han Chen; Peng-Cheng Huang; Liu-Wei Chen; Ming-Xian Zhang; Li-Hua Wang; You-Yong Zhu; Jia-Guan Wang; Yu Zhao (BMC Plant Biology)
Abstract Background Tinospora sagittata, a member belongs to the genus Tinospora of Menispermaceae family. Its tuberous roots have been used as traditional Chinese medicine (TCM) for pharmacological properties and are commonly known name as “Jin Guo Lan”. Although its plastome and nuclear genome had been sequenced, its mitochondrial genome has not been explored, which significantly hampers conservation efforts and further research for this species. In addition, previous efforts based on multiple molecular markers providing profound insights into an intergeneric phylogenetic framework for Burasaieae and sampled species of T. sagittata are placed in a superclades, species delimitation of T. sagittata still need to be comprehensively evaluated. Results Flow cytometry revealed that Tinospora sagittata has two cytotypes and a wide range in genome sizes. We further sequenced and assembled the organelle genomes of T. sagittata, including the mitogenome (513,210–513,215 bp) and plastome (163,621–164,006 bp). The plastomes were highly similar in gene content and exhibited a typical quadripartite structure, but a translocation as well as two inversions were detected in mitogenomes. The repeats patterns in both organelles are generally similar, but significant difference in the codon bias of the genes of Tinospora organelle genomes. Interesting, both organelle genomes had shown that inter-gene spacer regions could be used as effective molecular markers for further phylogenetic analyses and species identification. Comprehensive analysis of protein coding genes of organelle genomes showed that significant difference in Ka, Ks, and Ka/Ks values among the organelle genomes. Phylogenetic analysis identified a tree that was basically consistent with the phylogeny of Ranunculales described in the APG IV system. Conclusions We provided a high-quality and well-annotated organelle genome for Tinospora sagittata. The study present here advances our understanding of the intricate interplay between plastome and mitogenome. Moreover, our results also laid the foundation for further studying the course, tempo and mode of organelle genome evolution of Menispermaceae.